1974
DOI: 10.1111/j.1755-3768.1974.tb00370.x
|View full text |Cite
|
Sign up to set email alerts
|

Electro‐oculography in Albinos

Abstract: EOG recordings in groups of 30 normal Caucasian subjects, six normal Negroes and six albinos have been evaluated. Compared with the normal Negro and Caucasian subjects the albinos showed a generally low base value for the EOG amplitudes, a delayed rise in the light phase and an earlier occurrence of the dark trough, whilst the EOG ratio itself was unaffected.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

1976
1976
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…Recent studies have suggested that the RPE dysfunction in Best disease results from a disruption in Ca2 + -dependent Cl – channels through intracellular Ca2 + signaling. 31 Interestingly, two studies also recorded EOG in patients with ocular albinism (OA) and oculo-cutaneous albinism (OCA) and found a normal or supra-normal LP/DT ratio with significantly low DT amplitudes, 32 , 33 strikingly similar to the pattern found in patients with NF1, whereas albinism could appear as the clinical opposite of NF1. The authors proposed that these results could be explained by the abnormal melanosomal biogenesis and light-induced retinal damage.…”
Section: Discussionmentioning
confidence: 68%
“…Recent studies have suggested that the RPE dysfunction in Best disease results from a disruption in Ca2 + -dependent Cl – channels through intracellular Ca2 + signaling. 31 Interestingly, two studies also recorded EOG in patients with ocular albinism (OA) and oculo-cutaneous albinism (OCA) and found a normal or supra-normal LP/DT ratio with significantly low DT amplitudes, 32 , 33 strikingly similar to the pattern found in patients with NF1, whereas albinism could appear as the clinical opposite of NF1. The authors proposed that these results could be explained by the abnormal melanosomal biogenesis and light-induced retinal damage.…”
Section: Discussionmentioning
confidence: 68%
“…Table V are difficult to interprete. Gahlot &. Hansen (1974) examined the EQG's of normal Caucasians, normal negroes and albinos.…”
Section: Discussionmentioning
confidence: 99%
“…Large variability of the results may be a combined effect of various causes difficult to control like the preceding adaptation state of the eyes, ocular protrusion, differences in electrode positions and in resistance of the skin and the periorbital tissues. Also Number of eyes studied Adams 1973Babel et al 1977Gahlot & Hansen 1974Geijer-Mannerfelt & Pallin I968 Hohne 1974Jones et al 1977Kolb 1965Krogh 1977avan Lith & Balik 1970Lobes 1978Markoff et al 1981Pinckers 1979Reeser et al 1970Zonneveldt & van Lith 1980 the common stimulants tobacco and coffee are shown to have effect on EOG (Schmidt 1976). Due to the large scatter in results EOG is considered rather a qualitative than a quantitative test (Krogh 1977b).…”
mentioning
confidence: 97%